UPAYA TOURISM PROMOTION ORGANIZATION (TPO) FOR ASIA PASIFIC CITIES DALAM MENDUKUNG PARIWISATA INDONESIA DI KOTA SURABAYA PERIODE 2016-2021 - Ulfah Khulafah (Sekolah Tinggi Pariwisata Sahid Surakarta, 2022)
This article aims at the efforts of the Tourism Promotion Organization (TPO) for Asia Pacific Cities as an international organization that supports Indonesian tourism, especially in the city of Surabaya during 2016-2021. This article uses international organization theory and the concept of city branding. While the writing method used in this article is a qualitative descriptive method. Then the data collection is done by using interview techniques and literature study. The result of this study is that there is involvement of TPO as an international organization in encouraging tourism in the city of Surabaya. This can be seen from the function and role of TPO as an international organization which is divided into three, namely as a tourism marketing center, as a tourism information center and as a center for tourism networks and cooperation between cities. The third effort was realized through several programs such as TPO Travel Trade Events, magazine creation, and the existence of an international forum to accommodate opinions and cooperation between cities.